2005
DOI: 10.1002/elps.200500087
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of phenothiazines in cyclodextrin-modified capillary zone electrophoresis using sulfated cyclodextrins as chiral selectors

Abstract: In this study, enantioseparations of five phenothiazines, including promethazine, ethopropazine, trimeprazine, methotrimeprazine, and thioridazine, in CD-modified CZE using dual CD systems consisting of randomly sulfate-substituted CD (MI-S-beta-CD) and a neutral CD as chiral selectors in a citrate buffer (100 mM) at pH 3.0 were investigated. The results indicate that MI-S-beta-CD is an excellent chiral selector for enantioseparation of ethopropazine. The enantiomers of promethazine can also be baseline-resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…It was concluded that the differences in the binding constants and limiting mobility of the complexes were responsible for the enantiomer migration reversal with g-CD as chiral selector. Compared with the results obtained using a phosphate buffer, citrate buffer, which involved competitive complexation with chiral selector, should play a significant role in the enantiomer migration reversal [54]. Recently, enantioseparations of phenothiazines in CD-modified CE with randomly sulfate-substituted b-CD (MI-S-b-CD) and with dual CD systems consisting of MI-S-b-CD and neutral CDs as chiral selectors in a citrate buffer at pH 3.0 were reported [54].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…It was concluded that the differences in the binding constants and limiting mobility of the complexes were responsible for the enantiomer migration reversal with g-CD as chiral selector. Compared with the results obtained using a phosphate buffer, citrate buffer, which involved competitive complexation with chiral selector, should play a significant role in the enantiomer migration reversal [54]. Recently, enantioseparations of phenothiazines in CD-modified CE with randomly sulfate-substituted b-CD (MI-S-b-CD) and with dual CD systems consisting of MI-S-b-CD and neutral CDs as chiral selectors in a citrate buffer at pH 3.0 were reported [54].…”
Section: Introductionmentioning
confidence: 88%
“…Compared with the results obtained using a phosphate buffer, citrate buffer, which involved competitive complexation with chiral selector, should play a significant role in the enantiomer migration reversal [54]. Recently, enantioseparations of phenothiazines in CD-modified CE with randomly sulfate-substituted b-CD (MI-S-b-CD) and with dual CD systems consisting of MI-S-b-CD and neutral CDs as chiral selectors in a citrate buffer at pH 3.0 were reported [54]. MI-S-b-CD was found to be an excellent chiral selector for the enantioseparation of ethopropazine; the enantiomers of promethazine can be baseline resolved with MI-S-b-CD [54].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations